MOLECULAR DYNAMIC SIMULATION OF ASIATIC ACID DERIVATIVES COMPLEX WITH INDUCIBLE NITRIC OXIDE SYNTHASE ENZYME AS AN ANTI-INFLAMMATORY - MUSFIROH, IDA; KHATAMI, HANIFAHZIN; MEGANTARA, SANDRA; MUCHTARIDI, MUCHTARIDI (International Journal of Applied Pharmaceutics, 2021)
Objective: The aim of this study was to determine the stability interaction of asiatic acid derivatives (AA) complex with inducible nitric oxide synthase (iNOS) enzyme as an anti-inflammatory using Molecular Dynamic (MD) simulation. Methods: The methods were consisting of validation of molecular docking, molecular docking to calculate binding affinity within the complex between the compounds and iNOS enzyme by using MMGBSA (Molecular Mechanics/Generalized Born Surface Area), and MD system preparation, MD production as well as MD analysis using AMBER18. Results: The result of validation and molecular docking were AA5 has the most negative Gibbs energy that is -9.17 kcal/mol, which has better binding affinity than other derivatives than other derivatives. The molecular dynamics simulation of the modified structure of asiatic acid showed that binding energy value and RMSD of AA5, AA6 and AA9 have a lower value compared to arginine as a substrate of iNOS enzyme. Molecular Dynamics that have been occurred to the best three compounds chosen shown good result in terms of stability after 100 ns length simulation. And the lowest binding affinity has been achieved by a compound called AA5. Out of all ligands that have been simulated shown that their binding affinity was lower than AA5 that reached-44.6753 kcal/mol. Conclusion: This studies conclude that AA5 considerably more potential as a selective inhibitor of iNOS enzyme as an anti-inflammatory.